ASSOCIATIONS BETWEEN CUMULATIVE STRESS AND COGNITIVE FUNCTION IN HRS AND ELSA. (20th December 2022) - Chen, Ruijia; Lee, Harold; Okuzono, Sakurako; Kubzansky, Laura
Abstract: Despite growing research linking stressors with poorer cognition, less research explicitly considers stress from several sources, which often co-occurs and accumulate to influence health. We used the Global Gateway Harmonized data (HRS: n=8, 888; mean age: 74 years; ELSA: n=6, 715; mean age: 65 years) to examine whether higher cumulative stress is associated with lower levels of and faster decline in cognitive function. We fit linear mixed effect models to assess the stress-cognition associations. After adjusting for all covariates, baseline cumulative stress was associated with lower baseline cognitive function in both HRS (β=-0.02, 95%CI -0.04, -0.01) and ELSA (β=-0.03, 95%CI -0.05, -0.01). Unexpectedly, higher baseline cumulative stress was associated with slower cognitive decline in HRS (βtime*stress=0.001, 95%CI 0.002, 0.01) but not in ELSA. The stress-cognition associations may differ among adults in the US and the UK. Future research should investigate how cumulative stress may operate differently to influence cognitive function across different populations.